La relación entre los manuscritos 10 202 y 10 203 de la BNE, del "Árbol de las batallas" - Pascual, José A. (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 2018)
The relationship between two manuscripts from the National Library of Spain which include the translation that Antón Zorita did by commission from the first Marquis of Santillana is examined. There are clear evidences that one of the manuscripts, which is supposed to be the final version, is directly based in the other. The more significant corrections between both texts are to do with an attempt of leaving out features characteristics from the «aragonés» dialect.